2020
DOI: 10.1128/mbio.01153-20
|View full text |Cite
|
Sign up to set email alerts
|

The sps Genes Encode an Original Legionaminic Acid Pathway Required for Crust Assembly in Bacillus subtilis

Abstract: The crust is the outermost spore layer of most Bacillus strains devoid of an exosporium. This outermost layer, composed of both proteins and carbohydrates, plays a major role in the adhesion and spreading of spores into the environment. Recent studies have identified several crust proteins and have provided insights about their organization at the spore surface. However, although carbohydrates are known to participate in adhesion, little is known about their composition, structure, and localization. In this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 71 publications
(148 reference statements)
5
25
0
Order By: Relevance
“…S4 C-F). However, data were also in agreement with a previous study which deciphered the biosynthetic pathway of a Pse isomer: legionaminic acid (Leg) [ 95 ]. As this isomer should display the same fragmentation patterns under collision-induced dissociation (CID) as Pse, we considered m/z 333 in mutants as Leg.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…S4 C-F). However, data were also in agreement with a previous study which deciphered the biosynthetic pathway of a Pse isomer: legionaminic acid (Leg) [ 95 ]. As this isomer should display the same fragmentation patterns under collision-induced dissociation (CID) as Pse, we considered m/z 333 in mutants as Leg.…”
Section: Resultssupporting
confidence: 91%
“…S4 G, H). Finally, PEP depletion in pykA T>D likely result from Leg production as PEP is a precursor of Leg [ 95 ] and as metabolome data suggested that PEP concentration inversely correlates with Leg concentration (Fig. 3 C, D).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both of these proteins are involved in spore coat formation. 24 Supplementary Table 4 shows the fragmentation pattern of the SpsB–CotR cross-link.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Nevertheless, we have identified a ε-(γ)-glutamyl-lysine cross-link between SpsB (K 139 ) and CotR (Q 165 ) in wild-type spores, and as expected, it is absent in tgl spores. Both of these proteins are involved in spore coat formation Supplementary Table 4 shows the fragmentation pattern of the SpsB–CotR cross-link.…”
Section: Results and Discussionmentioning
confidence: 99%